2012
DOI: 10.18388/abp.2012_2167
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the human preadipocyte mitochondrial activity by beta-carotene.

Abstract: Increased ROS generation by the overload by metabolic substrates mitochondria paralleled by decrease of antioxidant activity are typical events found in metabolic syndrome and diabetes type 2. Metabolites of beta-carotene (BC) such as retinoic acid (RA), as well as low concentration of reactive oxygen species (ROS) modify the mitochondrial bioenergetic function. The aim of the study was to investigate the effect of beta-carotene on mitochondrial activity in human preadipocytes. BC used in concentrations, 10 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It was therefore thought that the use of antioxidant substances might prevent the development of diabetes and its related complications. Accordingly, antioxidants have shown positive effects in both type 1 and type 2 diabetes [26][27][28]. The present study showed that the different extracts from C. pentandra stem bark exhibited antioxidant activities on (DPPH), hemolysis of RBC, lipid peroxidation and˙OH radical.…”
Section: Discussionmentioning
confidence: 61%
“…It was therefore thought that the use of antioxidant substances might prevent the development of diabetes and its related complications. Accordingly, antioxidants have shown positive effects in both type 1 and type 2 diabetes [26][27][28]. The present study showed that the different extracts from C. pentandra stem bark exhibited antioxidant activities on (DPPH), hemolysis of RBC, lipid peroxidation and˙OH radical.…”
Section: Discussionmentioning
confidence: 61%
“…Beta-carotene is considered as a nutrient with an antioxidant activity that is able to quench singlet oxygen in skin, and thus protect it against harmful UV radiation. However, there are some studies conducted on skin cells that revealed that beta-carotene not only acts as an antioxidant but also has prooxidant potential, especially if its breakdown products are taken into account [ 37 , 38 , 39 ]. While beta-carotene pre-treatment alters the effects of H 2 O 2 -induced damage in erythro-myeloblastoid leukemia K562 cells [ 40 ], its metabolites such as retinal or retinoic acid causes oxidative stress with a decrease in mitochondrial membrane potential [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some studies conducted on skin cells that revealed that beta-carotene not only acts as an antioxidant but also has prooxidant potential, especially if its breakdown products are taken into account [ 37 , 38 , 39 ]. While beta-carotene pre-treatment alters the effects of H 2 O 2 -induced damage in erythro-myeloblastoid leukemia K562 cells [ 40 ], its metabolites such as retinal or retinoic acid causes oxidative stress with a decrease in mitochondrial membrane potential [ 38 , 39 ]. In contrast to other studied UV-absorbing compounds, hyperoside, which increases the viability of skin cells exposed to UV radiation and reduces ROS production, led to an even significantly greater depolarization of the mitochondrial membrane potential than that induced by UV radiation alone.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular ATP content was measured using an ATPlite™ Luminescence ATP Detection Assay System (Perkin Elmer, USA). The results were calculated as nmol ATP, adjusted for protein content, and reported as nmol ATP/g of protein (Sliwa et al 2012).…”
Section: Atp Assaymentioning
confidence: 99%